Class XI Students' Historical Awareness of Values KH Ahmad Dahlan's example at SMA Muhammadiyah 1 Semarang - Jannah, Ulfiah Afidatul; Ahmad, Tsabit Azinar (Universitas Negeri Semarang, 2022)
The purpose of this study was to identify the exemplary values of Ahmad Dahlan's leadership, which had been applied in the learning process, to prioritize the embedding of Ahmad Dahlan's values of exemplary in the learning process, and to analyze the obstacles of the learning process about Ahmad Dahlan's character. The method in this study was a qualitative type of case study. Informants were history teachers, teachers of Kemuhammadiyahan, class XI Muhammadiyah 1 High School Semarang. The results of this study indicate that KH Ahmad Dahlan has five values, as stated in Character Education Strengthening (KDP): religious values, independence, cooperation, nationalism, and integrity. The embedding of KH Ahmad Dahlan's exemplary value has been done quite well in the history of class XI learning Muhammadiyah 1 High School Semarang. Besides the history subject, the Kemuhammadiyahan subject also plays a vital role in cultivating KH Ahmad Dahlan's exemplary values in students. Obstacles in embedding K. H Ahmad Dahlan's exemplary values in the learning process, namely lack of use of the learning model used by teachers make students less interested in historical learning and lack of pedagogical competencies possessed by teachers so that the teacher has difficulties related to differences so much and also impossible that the teacher can understand the character of students one by one.